2013
DOI: 10.1021/la401931y
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of Hyaluronan Layers with Similarly Charged Surfaces: The Effect of Divalent Cations

Abstract: We used colloidal probe atomic force microscopy to measure the normal forces between the surface of a silica colloidal particle and a sparse layer of hyaluronan (hyaluronic acid, HA, MW ≈ 10(6) Da) covalently attached to a planar silica surface, both across pure water and following the addition of 1 mM MgCl2. It was found that in the absence of salt the HA layer repelled the colloidal silica surface during both approach and retraction. The addition of the MgCl2, however, changes the net force between the negat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 64 publications
(112 reference statements)
1
6
0
Order By: Relevance
“…The high concentration required suggests unspecific shielding of close opposing charges at both sides of the domain interface. Similar behaviour has been reported for surfactants, DNA and hyaluronan in the presence of Ca 2+ , and was termed the ‘divalent cation bridging effect’ .…”
Section: Resultssupporting
confidence: 64%
See 1 more Smart Citation
“…The high concentration required suggests unspecific shielding of close opposing charges at both sides of the domain interface. Similar behaviour has been reported for surfactants, DNA and hyaluronan in the presence of Ca 2+ , and was termed the ‘divalent cation bridging effect’ .…”
Section: Resultssupporting
confidence: 64%
“…It has been reported that divalent cations potentially form a bridge between oppositely charged carboxylate groups on polyelectrolytes, DNA or hyaluronic acid. Based on our data, this effect also influences domain interaction in CDH, and presumably also applies to other proteins, given that a number of negatively charged amino acid residues are present in close proximity at domain interfaces.…”
Section: Discussionmentioning
confidence: 99%
“…It is noted that this mass uptake includes the bound water which, according to a previous report, may take up to 99% volume fraction in a grafted HA layer. 27 The softness of each layer is directly linked to the energy dissipation per coupled unit mass, which in turn is in linear relationship with the Dd/Df ratio in Fig. 3(b).…”
Section: Qcm Characterisationmentioning
confidence: 97%
“…Using the calculation described previously 27 It was shown 47 that the ratio of osmotic pressures due to counterions and the excluded volume effects, Π c/i and Π exc respectively, is given by (Π c/i /Π exc ) ≈ i/ϕ, where i is the degree of ionization and ϕ is the volume fraction of monomers in the compressed polymer layers.…”
Section: Osmotic Pressure and Surface Excess Of Ha Layermentioning
confidence: 99%
“…Effective interactions between polyelectrolytes in salt solutions have attracted rather attention and have been studied extensively in recent years [42][43][44][45][46][47][48][49][50]. The intrinsic repulsions between like-charged polyelectrolytes can be modulated into effective attractions by multivalent counterions, which is generally attributed to the bridging effect or the Coulomb depletion effect of condensed counterions [51][52][53][54][55][56][57][58][59][60][61][62][63][64][65]. For oppositely charged polyelectrolytes, the intrinsic attractive interaction can be mediated into apparent repulsions by nonsymmetrical 1:2 or 1:3 salt due to the respective underneutralization and over-neutralization of the oppositely charged polyelectrolytes by their respective counterions [66][67][68][69][70][71].…”
Section: Introductionmentioning
confidence: 99%